An Analysis of Teachers’ Perceptions in Developing Elementary School Students’ Creative Thinking through Science Learning Media - Cahyaningsih, Ratna Dila; Ningsih, Mariza Putri Sari Dewi (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The research objective was to analyze teachers’ perceptions in fostering elementary school students’ creative thinking through science learning media. The data analysis was expected to help teachers find out science learning media in developing students' creative thinking skills that can be used in learning activities as a complement to books that have been used following the characteristics and the surrounding environment. The research method was qualitative research with data collection techniques conducted through interviews and questionnaires. The research subjects were 12 elementary school teachers who used science learning media to implement learning activities. The research results showed that students could use science learning media in developing creative thinking, but it had not been implemented optimally. Therefore, it was crucial to be able to develop it. In addition, the science learning media could be developed based on elementary school students’ characteristics in the concrete operational stage and the scope of material related to the environment around students. Science learning media can be displayed in digital form to develop students' creative thinking.